(untitled) (Sains Humanika, 2018)
This paper discusses the lack of forest resource resources for sustainable tourism of the Mah Meri tribe Orang Asli tourism. The study was conducted at Sungai Bumbum Village. In-depth interviews are used as a method of data collection of case studies. This study uses purposive sampling and data is collected using in-depth and detailed structured interviews. This study is important because studies related to indigenous tourism are still not widely explored, especially in Malaysia. Travel products from forest resource sources such as woodcarving and weaving are an important product that leads to sustainable tourism development holistically. The study also revealed that the Orang Asli community of the Mah Meri tribe was increasingly worried about the extinction of forest product resources arising from the various developments conducted on Carey Island. The Indigenous Peoples of Mah Meri also feel that their culture and tourism have gradually been facing major threats due to the lack of forest resources. However, it is hoped that the findings of this study will contribute to the sustainability of sustainable tourism on Carey Island, Malaysia. Â